Physical and Chemical Characteristics of Soil in the Habitat of Gymnostoma rumphianum (Miq.) L.A.S. Johnson in Tojo Una-Una Regency, Central Sulawesi - Rahmawati; Yusran; Zulkaidhah; Retno Wulandari; Rukmi; Ramadanil Pitopang (Jurnal Penelitian Pendidikan IPA, 2026)
Sulawesi, particularly the Wallacea region, has a unique yet extreme ultramafic ecosystem for vegetation growth due to nutrient limitations and high heavy metal concentrations. This study aims to analyze the characteristics of the physical and chemical properties of the soil in the habitat of Gymnostoma rumphianum (Miq.) L.A.S. Johnson in Tojo Una-Una Regency, Central Sulawesi. The study was conducted in Betaua and Podi Villages by dividing the locations based on distance from the river flow. Physical parameters analyzed included bulk density, soil texture, and permeability, while chemical parameters included N, P, K, pH, organic C, C/N ratio, and electrical conductivity (DHL). The results showed that the soil texture in Betaua Village was dominated by sand fractions, while Podi Village was dominated by silt fractions due to the influence of river sedimentation. Chemically, the soil is alkaline (pH 8.05–8.28) with low to very low nitrogen and phosphorus content, but has moderate potassium availability. The presence of G. rumphianum, an actinorhizal plant capable of fixing nitrogen, is a key factor in the adaptation and sustainability of vegetation in this marginal land. This study concludes that despite extreme edaphic constraints, soil-plant interactions and local environmental dynamics such as fluviality significantly determine the structure of the ultramafic habitat in the region.